A planar ultrawideband elliptical monopole antenna with reflector for breast microwave imaging. Issue 4 (April 2014) - Latif, Saeed; Flores‐Tapia, Daniel; Pistorius, Stephen; Shafai, Lotfollah
ABSTRACT A printed elliptical monopole antenna operating at 1–4 GHz frequency for biomedical imaging applications is presented in this article. To reduce the reflection of the microwave signal from breast, glycerin is used as the coupling medium (εr = 9, σ = 0.4 S/m, tan δ = 0.28) whose electrical properties are close to those of breast tissue. Directional patterns and reduced back radiations are achieved using a reflector. The antenna has wide impedance bandwidth from 1 GHz to over 6 GHz (over 140%), suitable for radar‐based imaging. The antenna demonstrates S21 > −60 dB from 1 to 4 GHz in the coupling medium. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:808–813, 2014